Pengaruh Integrasi Game Edukatif dan Reward terhadap Motivasi Belajar Siswa Sekolah Dasar - Syafiqa Octora; Shella Nerisa; Lia May; Fita Mar'atus; Titania Afriza; Delia Indrawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates the effect of educational games and structured rewards on the learning motivation of fifth-grade students at SDN Sempol Magetan. Using a quasi-experimental design with experimental and control groups, this study assumes that active engagement and positive reinforcement play an important role in enhancing both intrinsic and extrinsic motivation. In its implementation, students in the experimental group were provided with game-based learning aligned with the subject matter, along with a structured reward system as a form of appreciation for their learning achievements, while the control group participated in conventional learning without these interventions. The results of the quantitative analysis show that the use of educational games significantly increased students’ learning motivation in the experimental group, with an average motivation score of 5.708 and with a significance value of p<0.05. These findings indicate that integrating games and rewards into the learning process has the potential to improve students’ engagement, enthusiasm, and active participation in classroom activities. In addition, students also demonstrated improvements in self-confidence and persistence in completing assigned tasks. Interestingly, in the control group, there was also a significant change in learning motivation between the pretest and posttest (p<0.05), even without the game and reward intervention. This suggests that other contextual factors, such as the teacher’s role, learning environment, and social interaction among students, also contribute to the dynamics of learning motivation. Pedagogically, educational games represent an effective instructional innovation to enhance student motivation, and further research is recommended to examine the mediating and moderating mechanisms of the effects of games and rewards, as well as to identify other contextual components that influence student learning motivation more comprehensively.